2017
DOI: 10.1109/jtehm.2017.2695194
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Imaging for Detecting Caries and Structural Deformities in Teeth

Abstract: 2-D radiographs, while commonly used for evaluating sub-surface hard structures of teeth, have low sensitivity for early caries lesions, particularly those on tooth occlusal surfaces. Radiographs are also frequently refused by patients over safety concerns. Translucency of teeth in the near-infrared (NIR) range offers a non-ionizing and safe approach to detect dental caries. We report the construction of an NIR (850 nm) LED imaging system, comprised of an NIR source and an intraoral camera for rapid dental eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“… 11 , 12 Many existing studies indicate that near-infrared (NIR) light looks more promising than visible light for the development of novel dental optical imaging techniques. 13 18 As the only Food and Drug Administration (FDA)-approved NIR fluorescence dye for clinical usage in fluorescent angiography, indocyanine green has been widely used in many other fields, like cancer or dental imaging. 11 , 19 27 Our previous studies have successfully demonstrated ICG-NIR fluorescence (ICG-NIRF) dental imaging in both human-extracted tooth and rat models.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 Many existing studies indicate that near-infrared (NIR) light looks more promising than visible light for the development of novel dental optical imaging techniques. 13 18 As the only Food and Drug Administration (FDA)-approved NIR fluorescence dye for clinical usage in fluorescent angiography, indocyanine green has been widely used in many other fields, like cancer or dental imaging. 11 , 19 27 Our previous studies have successfully demonstrated ICG-NIR fluorescence (ICG-NIRF) dental imaging in both human-extracted tooth and rat models.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has detailed an approach using an RGB oral endoscope image [8,9]; however, most approaches cannot provide a detailed structure of the tooth, especially the tooth root, and therefore struggle to provide caries diagnosis. Compared to oral endoscope imaging, dental radiographs provide greater image quality and detect detailed structure deformity in the tooth [10]; therefore, the dental radiographic image is the most well-known approach, and is preferable for the detection of caries in the early stage.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent times, the medical image processing provides various detection techniques for detecting the dental caries in an early stage [1]. The dental decay or tooth decay is generally referred to as dental caries, and this disease takes place in the hard tissue of the tooth due to the action of the micro-organisms.…”
Section: Introductionmentioning
confidence: 99%
“…When the dental caries is larger in size, they can be viewed by naked eye, whereas, smaller lesions are difficult to identify. In the primary level of diagnosis, all the tooth surfaces of the patient are inspected by utilizing a light source, dental mirror and explorer [5, 6, 7]. Most of the diagnosis is made with the Dental radiographs (X-rays), and they are efficient in exhibiting the dental caries that takes place between the teeth [19, 20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation